Experimental Evidence for Heavy-Atom Tunneling in the Ring-Opening of Cyclopropylcarbinyl Radical from Intramolecular (12)C/(13)C Kinetic Isotope Effects - Gonzalez-James, Ollie M. (2010)
[Image: see text] The intramolecular (13)C kinetic isotope effects for the ring-opening of cyclopropylcarbinyl radical were determined over a broad temperature range. The observed isotope effects are unprecedentedly large, ranging from 1.062 at 80 °C to 1.163 at −100 °C. Semi-classical calculations employing canonical variational transition state theory drastically underpredict the observed isotope effects, but the predicted isotope effects including tunneling by a small-curvature tunneling model match well with experiment. These results and a curvature in the Arrhenius plot of the isotope effects support the recently predicted importance of heavy-atom tunneling in cyclopropylcarbinyl ring-opening.